Ewolucja paradygmatów nauk o zarządzaniu. Między refleksją a działaniem - Antczak, Zbigniew (Evolution of paradigms in the management science, 2005)
The author presents a report including selected opinions in the discussion on paradigms and presents his own reflections on the subject.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 99-105